EFFECT OF EICHORNIA WATER WEED ON PHYSIOLOGICAL INDICATORS OF GOATS - Nakhalboyev Alisher Aliboyevich; Eshimov Dusmurat; Nuridinova Mukhlisa Isomiddin kizi (Bright Mind Publishing, 2025)
In the articlegoat dietWhen supplemented with eichhornia seaweed, goats' productivity, immune system, and milk production are improved.impact on the amount information is provided about.
Keywords: Amino acid, physiological state sugar, organism, coefficient Eichornia crassipes, fatty acids, minerals, vitamins, diet, milk heredity, protein.